Lipofection of single guide RNA targeting MMP8 decreases proliferation and migration in lung adenocarcinoma cells - Maradiaga, Oscar David Hernandez; Mok, Pooi Ling; Sivapragasam, Gothai; Samrot, Antony V.; Ali Khan, Mohammed Safwan; Aisha Farhana; Alzahrani, Badr; Tong, Jiabei; Karuppiah, Thilakavathy; S. Joseph, Narcisse M.; Subbiah, Suresh Kumar (MDPI AG, 2021)
Background and Objectives: Matrix metalloproteinases (MMP) have been implicated as major determinants of tumour growth and metastasis, which are considered two of the main hallmarks of cancer. The interaction of MMP8 and other signalling molecules within and adjacent tumoral tissues, including immune cells, are rather elusive, particularly of adenocarcinoma cell type. In this study, we aimed to investigate the role of MMP8 in non-small cell lung cancer proliferation and invasiveness potential. Materials and Methods: We individually lipofected with two different single guide RNA (sgRNAs) that specifically targeted on MMP8, with CRISPR-Cas 9 protein into the cells. Results: Our results clearly indicated that the lipofection of these complexes could lead to reduced ability of A549 cells to survive and proliferate to form colonies. In addition, when compared to non-transfected cells, the experimental cell groups receiving sgRNAs demonstrated relatively decreased migration rate, hence, wider wound gaps in scratch assay. The quantitative real time-polymerase chain reaction (qRT-PCR) demonstrated significant reduction in the MAP-K, survivin and PI3-K gene expression. MMP8 might have protective roles over tumour growth and spread in our body. Conclusions: The delivery of sgRNAs targeting on the MMP8 gene could induce tumour cell death and arrest cell migratory activity.